الخصائص السّيكومتريّة لمقياس اتّخاذ القرار "لأسماء أبو المجد أحمد محمد" لدى مديري مرحلة التّعليم المتوسّط دراسة ميدانية بمتوسّطات ولاية المسيلة - طيباوي علي; عيواز وسيلة; اشراف: العمرية بن عمرة (جامعة محمد بوضياف -المسيلة, 2025)
تهدف الدّراسة إلى التّحقّق من الخصائص السّيكومترية (الصّدق، الثّبات) لمقياس اتّخاذ القرار لدى مدراء مرحلة التّعليم المتوسّط بمتوسّطات ولاية المسيلة، ولتحقيق أهداف الدّراسة تم استخدام المنهج الوصفي، وتمثّلت عينة الدراسة في (153) مديرًا ومديرةً ولتحقيق أغراض الدّراسة قام الطالبان بتطبيق مقياس "اتّخاذ القرار للباحثة "أسماء أبو المجد" على المدراء، وقد قاما بحساب الخصائص السّيكومتريّة له، ولمعالجة البيانات إحصائيًا تمّ الاعتماد على برنامج الرّزم الإحصائيّة للعلوم الاجتماعيّة (Spss) واستخدام الأساليب التّالية: معامل الارتباط بيرسون، معامل الارتباط سبيرمان براون، وألفا كرونباخ. حيث توصّلت الدّراسة إلى النّتائج التالية: - ثبات المقياس وذلك عند حسابه بطريقتين أولاً: ألفا كرونباخ، والتي قدرت قيمته (0,92) وهي قيمة مرتفعة، ثانيًا: طريقة التجزئة النّصفيّة، والتي قدرت قيمته بـ (0,91)، كما توصّل الطالبان إلى صدق المقياس، وذلك بعد حسابه بطريقة: الاتّساق الدّاخلي من حيث حساب معاملات الارتباط بين البند والدّرجة الكليّة والتي تراوحت بين (0,868-0,24) وبين البند والمحور حيث كانت معاملات الارتباط كلّها قويّة ودالة إحصائيًا عند (0,000) وبين المحور والدرجة الكلية حيث كانت كلّها قويّة ودالة عند (0,000)، بالإضافة إلى طريقة التّحليل العاملي الاستكشافيّ لحساب الصّدق. وبعد التّحليل تبين تشبّع ستة محاور مما يدل على صدق المقياس. الكلمات المفتاحية: الخصائص السيكومترية، مقياس اتخاذ القرار، المدراء. Abstract: The study aimed to verify the psychometric properties (validity and reliability)of the decision ــ making scale for middle school principals according to the averages of the state of M'Sila. To achieve the objectives, the study, the descriptive method was used on a sample of middle school principals, whose number was (153) male and female principals. To achieve the purposes of the study the researcher applied the "Decision Making" scale of the researcher "Asmaa Abu Al-Majd" on politeness and he calculated its psychometric properties and to process the data statistically, reliance was placed on the Statistical program for Social Sciences (SPSS) the the following statistical methods were used: Pearson correlation coefficient, Spearman-Brown correlation coefficient, and where the study reached the following results: - The reliability of the scale when it is calculated using two methods. Firstly, Alpha Cronbach Method, whose value was estimated at (0.92), which is a high value. Secondly, The halving method, whose was estimated at (0.91). - The researchers confirmed the validity of the scale after calculating it using the internal consistency method in terms of calculating the correlation coefficients between the item and the total score, which ranged between (0.868-0.24) and between the item and the axis, where the correlation coefficients were all strong and statistically significant at (0.000) and between the axis and the total score, where they were all significant and strong at (0.000), in addition to the Method of factor analysis to escplore the validity. After the analysis, it was found that six axes were saturated, which indicates the validity of the scale. Key words: Psychometric properties, decision making, head master.